When the Road Is Covered in Nails: Making Sense of Madness in an Urban Mosque. (18th December 2019) - Prickett, Pamela J
Abstract: This study returns to the classic interactionist approach of earlier work on mental illness to understand how communities attribute nonconforming behaviors as symptoms of mental illnesses and how their informal labels shape the ways in which they interact with people perceived as ill. It draws on six years of in-depth fieldwork in a low-income urban mosque community, where members frequently interacted with fellow Muslims they labeled "crazy." Through repeated interaction, members come to understand madness as part of living in a poor neighborhood and then perceive themselves as also at risk of developing mental health problems. Many members avoided getting close to people with mental illnesses, but their shared religious identities meant that at the end of life someone who had previously been excluded from social networks could receive burial care. I discuss the implications of their responses for understanding the role of community care.